One today a poem for Barack Obama's presidential inauguration January 21, 2013 - Blanco, Richard 1968- (University of Pittsburgh Press, 2013)
The author was selected by President Obama to be the fith inaugural poet. He is the youngest person and the first Latino and openly gay man to have received this honor